A Legal Review of the Implementation of Government Goods and Services Procurement in Sibolga City from the Perspective of Transparency and Accountability Principles Pursuant to Presidential Regulation Number 16 of 2018 - Feby Sri Audina; Onny Medaline (Yayasan Multidimensi Kreatif, 2026)
This research examines the implementation of goods and services procurement within the Sibolga City Government (Pemko Sibolga) from the perspective of transparency and accountability principles as mandated by Presidential Regulation Number 16 of 2018 on Government Procurement of Goods/Services (Perpres 16/2018), as subsequently amended by Presidential Regulation Number 12 of 2021. The research employs a normative legal research methodology utilizing three approaches: the statutory approach, the conceptual approach, and the case approach. Legal materials consist of primary legal materials comprising statutory regulations, secondary legal materials comprising doctrines, scientific journals, and state institution reports, and tertiary legal materials comprising legal dictionaries and encyclopedias. The research yields three principal findings. First, Perpres 16/2018 normatively accommodates the principles of transparency and accountability comprehensively through an SPSE-based e-procurement mechanism, the mandatory publication of the General Procurement Plan (RUP) through SiRUP, the establishment of a permanent and structural Procurement Work Unit (UKPBJ), a structured protest mechanism, and a multi-layered oversight system involving APIP, BPK, KPK, and DPRD. Second, the implementation of transparency and accountability principles in Sibolga City Government procurement continues to face significant obstacles, including: limited UKPBJ human resources holding procurement competency certificates; suboptimal utilization of SPSE and SiRUP due to information technology infrastructure limitations; weak public complaint mechanisms and whistleblower protection; the absence of a Procurement Agent to assist OPDs with limited capacity; and insufficiently optimal legislative oversight by the Sibolga City DPRD over the procurement process. Third, these obstacles originate from a combination of factors relating to legal substance, law enforcement capacity, facility and infrastructure limitations, and bureaucratic culture, as explained by Soerjono Soekanto's legal effectiveness theory. The research recommends: issuance of a Mayoral Regulation specifically governing UKPBJ, regulating career progression and functional allowances for procurement positions; acceleration of procurement competency certification programs for all PPK, Election Working Group, and Procurement Officers; strengthening of information technology infrastructure supporting SPSE; establishment of a public-friendly complaint system with confidential whistleblower protection; and reinforcement of the oversight functions of the Sibolga Regional Inspectorate and DPRD.